EXPERIMENTAL STUDY OF BORATE-BASED GLASS MEDIUM MATERIAL AND HUTA GINJANG QUARTZ SAND THROUGH MELT-QUENCHING TECHNIQUE - Pangabean, Jonny Haratua; Hutahaean, Juniar; Sihombing, Luli Warty; Doloksaribu, Maryati Evivani; Rajagukguk, Juniastel (EINSTEIN (e-Journal), 2025)
This research aims to produce a glass material based on quartz sand and borate compounds that can later be applied as a host matrix of rare earth ions as optical amplifiers. The research stages began with exploring quartz sand from Huta Ginjang, cleaning, grinding using a ball-mill and mixing with several other compounds namely Boron oxide (B(2) O3), barium oxide (BaO) and sodium oxide (Na2) O. The calculation and weighing process is carried out to obtain the mass of each compound to be used. The composition of each compound is shown through the chemical formula (x)Quartz sand + (60- x)B(2)O(3)+ 10BaO + 30Na2O (where x = 0; 2.5; 5; 10; 15; 20 mol%). The next step is the melting and molding process using the melt-quenching method. Through this experiment, a homogeneous and more transparent glass medium with optimum composition for each former and modifier compound was obtained.